Modelling of pedals pressing mechanisms for low speed driving in road traffic delay - Md Isa, Hazril; Ahmad, Salmiah; Abdullah, Muhammad; Rahman, Mohammed Ataur; Abd Ghani, Nur Maniha; Mohd Noor, Nurul Muthmainnah (2022)
Road traffic delay is imminent in big cities around the world including Kuala Lumpur, due to the increase in vehicle ownership, weather condition, road blocks by authorities and ongoing infrastructure projects at particular point of the road. Previous literature shows that the average time spent by drivers in driving under road traffic delay is about 30-53 minutes per day. Within the delay, regular pressings of the brake and accelerator may lead to leg and body fatigue, hence may give detrimental effect on the driver in the long run. This paper aims to mimic the pedal pressing and releasing mechanism in replacing the leg activities during road traffic delay, such that the driver will no longer need to recurrently pressing both pedals, thus reduce the fatigue. In replicating the pressing mechanism, a linear electromechanical actuator is designed for this purpose due to its high force density as well as good response time. The mathematical model of the actuator is first developed and integrated with car dynamic model in Simscape model. All parameters used for simulation purposes were taken from an actual electromechanical actuator used for the similar application. Simulation performance evaluation was conducted on a virtual environment for the integrated models and the response of the models were investigated. As a result, the actuator model is capable to produce the desired output force that is similar with human leg during pressing activity, with about 200 N force. The model was coupled with tuned PID controller, and the actuator was also able to produce an acceptable time response, where the vehicle is brought to a complete stop within less than 1 second, which is closed to the actual driver’s leg activities during the pedal pressing in a road traffic delay.